Accessibility of children with special health needs to the health care network - Eliane Tatsch Neves; Aline Cristiane Cavicchioli Okido; Fernanda Luisa Buboltz; Raíssa Passos dos Santos; Regina Aparecida Garcia de Lima (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: To know how children with special health needs access the health care network. Method: This is a qualitative research of descriptive-exploratory type, developed using semi-structured interviews mediated by the Talking Map design. Participants were 19 family caregivers of these children in two Brazilian municipalities. Data were submitted to inductive thematic analysis. Results: Difficulties were mentioned from the diagnosis moment to the specialized follow-up, something represented by the itinerary of the c hild and his/her family in the search for the definition of the medical diagnosis and the access to a specialized professional; a gap between the children's needs and the care offered was observed in primary health care. Conclusion: The access of children with special health needs is filled with obstacles such as slowness in the process of defining the child's diagnosis and referral to a specialist. Primary health care services were replaced by care in emergency care units.